Model Bimbingan Pra Nikah Berbasis Cyber Education bagi Mahasiswa - Zen, Ella Faridati; Puspitasari, Dwi Nikmah; Multisari, Widya; Probowati, Devy; Sulaiman, Hamidah binti (citeus, 2025)
Pre-marital guidance in the Bride and Groom Course is considered not effective in preparing prospective brides, as evidenced by the high number of divorce cases. An innovative breakthrough is needed in helping the prospective bride and groom to be ready and mature to build a household. This study aims to produce a model of pre-marital guidance based on cyber education. The research design adapts the procedural model including determining the problem, planning, designing a product prototype, testing and revising the product. The research subjects were 280 students from universities in the Java region. The test subjects consisted of 2 material experts and 1 learning resource developer expert. The instrument is in the form of a questionnaire for pre-marital guidance material needs as well as a product assessment format. The development of producing pre-marital guidance model products, manifested in the form of Handbooks, Material Books and multimedia, is used for online pre-marital guidance services, through the Massive Open Online Courses (MOOC) platform. The material expert's assessment resulted in an index of 0.9 in the manual and 1.0 in the material book. Meanwhile, product evaluation by expert learning resource developers averaged 3.8 in the manual format and 3.85 in the pre-marital guidance multimedia. The Cyber ​​Education-based Pre-Marriage Guidance Model fulfills a very high level of acceptance. The pre-marital guidance model is theoretically acceptable through expert testing, so that it can be used in online pre-marital guidance services in tertiary institutions.